ANALYSIS OF FISHERY REVENUE OF BROWN CITIZEN VILLAGE HEALTH PALOLO DISTRICT SIGI DISTRICT - H. Mustamir, .; H. Munayang, Olivia; Parmita, Ririn (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2018)
This study aims to determine the income of red curly chili farmers in the village of Happy Sub-district Palolo Sigi District. Data collection method used is survey method to obtain primary data directly from original source. The process of data analysis in this research is done qualitatively and quantitatively. The population in this study is all red curly chili farmers in the village of Happy Sub-district Palolo Sigi District. The sample in the study was taken through incidental sampling approach. The results showed that the acceptance of red curly pepper with a half acre of land that is equal to Rp. 56.705.000,00 with profit ratio of 3 times. Acceptance of red curly peppers with a land area of one-third hectare is Rp. 50.195.500,00 with profit ratio of 2.69 times. Acceptance of red curly pepper with a land area of one quarter hectare is Rp. 43.736.500,00 with a profit ratio of 4 times. This indicates that the income of red curry chili farmers in the village of Happy Sub-District Palolo Sigi Regency is better income.Â